Ability of Sandy Soil to Retain Water in Various Coastal Sand Land Management Practices in Bugel Village, Kulon Progo Regency: Kemampuan Lahan Pasir Menahan Air pada Berbagai Praktik Pengelolaan Lahan di Desa Bugel Kabupaten Kulon Progo - Tri Nursasomo, Muhammad; Nurcholis, Mohammad (Jurnal Ilmu Tanah dan Air, 2025)
The reduction of agricultural land due to land conversion has compelled farmers to explore alternative cultivation areas such as coastal sandy soils, despite their limited water retention capacity. Agricultural land in Bugel Village, Kulon Progo Regency, is predominantly composed of sand and exhibits various land management practices. This study aims to analyze the influence of land management strategies on the water retention capacity of coastal sand soils and to identify related soil properties. Soil samples were collected through purposive sampling based on land use maps and direct observation, resulting in three sampling locations that represent different land management practices. Descriptive statistical methods were employed, and the data were analyzed using Analysis of Variance (ANOVA) followed by the Duncan Multiple Range Test (DMRT). The results showed a significant difference in permanent wilting point moisture content (P < 0.01), available moisture content (P < 0.05), and air-dried moisture content (P < 0.05). These findings underscore the importance of appropriate land management in enhancing the water-holding capacity of coastal sandy soils.